ANALISIS PEMILIHAN SUPPLIER PRODUK PETI MATI MENGGGUNAKAN METODE FUZZY ANALYTICAL HIERARCHY PROCESS & TOPSIS - Wijayanthi, Veronica; Ahmad; Doaly, Carla Olivia (Jurnal Mitra Teknik Industri, 2023)
This company is a company engaged in the coffin industry since 2014. In today's technological developments, there are many cases of competition, one of which is in business. To maintain his business, one of his efforts is to choose the right supplier. The challenge in finding the right supplier is the supply or procurement of the right product for consumers, at the right time at an affordable price. In selecting this supplier, many criteria can be taken into consideration, making it a difficult decision. Thus, this research was conducted to achieve the goal of getting which suppliers the company will maintain to work with by implementing Multiple Criteria Decision Making (MCDM) using Fuzzy AHP and TOPSIS. Where the Fuzzy AHP method is used to minimize uncertainties that can occur in decision making, while the TOPSIS method is used to find alternative solutions that have the shortest distance to positive and negative ideal solutions. Supplier selection is carried out by considering 5 qualities, 10 sub-criteria, and 4 alternative suppliers. The results of the Fuzzy AHP calculation show that the first rank is S4 with a weight of 0.498, followed by S1 with a weight of 0.196, S2 with a weight of 0.172, and S3 with a weight of 0.133. Whereas in the TOPSIS calculation, S4 was obtained as the first rank with a weight of 0.665; followed by S1 with a weight of 0.433, S2 with a weight of 0.244, and S3 with a weight of 0.178.